Problems in Organizing Independent Study Activities in Physics Classes - U. N. Sultonova; S. N. Sultonov (International Journal on Integrated Education, 2022)
Physics is an intersection of all disciplines, closely intertwined with other disciplines. It is no coincidence that an American scientist says that everything has physics. Therefore, today the issue of perfect teaching of this subject not only in schools but also in higher education institutions is of great importance. In this article, the author describes in detail the methodology and importance of teaching world science, as well as the material and spiritual role of physics for students.